Peripheral and non-peripheral-designed multifunctional phthalocyanines; synthesis, electrochemistry, spectroelectrochemistry and metal ion binding studies - KOCA, ATIF (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
A novel type of ionophore ligands, 3'-(2,3-dihydroxypropylthio)-phthalonitrile and 4'(2,3-dihydroxypropylthio)-phthalonitrile, and their alpha- and beta-tetrasubstituted metallo phthalocyanines, (MPc), (M = Zn-II, Co-II, (MnCl)-Cl-III, (FeAc)-Ac-III, Cu-II) have been prepared and fully characterized by elemental analysis, FT-IR, H-1 and C-13 NMR, and MS (ESI and Maldi-TOF). The complexes are soluble in both polar and non-polar solvents, such as MeOH and EtOH, THF, CHCl3 and CH2Cl2. The spectroscopic properties of the complexes are affected strongly by the electron-donating sulfanyl units on the periphery of the phthalocyanines. The cation binding properties of the complexes, for example using Ag-I and Pd-II, were evaluated by UV-Vis spectroscopy and the results show the formation of polynuclear phthalocyanine complexes. Functional donors on the periphery of the zinc and copper complexes coordinate to Ag-I and Pd-II to give ca. a 2:1 metal-phthalocyanine complex binding ratio for the concentration of 2.5 x 10(-5) M (Pc) and 1.0 x 10(-3) M (Metal ions). Voltammetric and in-situ spectroelectrochemical studies were performed to characterize the redox behavior of the complexes. An in-situ electrocolorimetric method was applied to investigate the colors of the electro-generated anionic and cationic forms of the complexes. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Phthalocyanines; Aggregation; Metal sensor; Electrochemistry; In-situ spectroelectrochemistry; In-situ electrocolorimetry; SUBSTITUTED COBALT; MANGANESE; BEHAVIOR; PORPHYRAZINES; SPECTROSCOPY; VOLTAMMETRY; HYBRID; IRON